S33 Duration and nature of symptoms prior to asthma diagnostic testing in a paediatric population. (11th November 2022) - Machin, S; Gallacher, E; Bennett, M; Healy, L; Tudge, R; Lowe, L; Kerry, Gina; Wang, R; Fowler, ST; Simpson, A; Murray, C
Abstract : Background: Asthma is very common in UK children. It involves hyperresponsiveness of airways, leading to symptoms such as cough, breathlessness, chest tightness and wheeze. However, there is little evidence on the specific prevalence and duration of symptoms in children prior to consideration for asthma diagnostic testing. Aim: To investigate the prevalence and duration of symptoms in children who are being referred for asthma diagnostic testing and to identify whether this varied according to subsequent diagnosis. Method: Treatment naïve children (age 5–16 yrs) with suspected asthma, were referred by primary care physicians in south Manchester to the Rapid Access Diagnostics for Asthma (RADicA) study for assessment including clinical history followed by extensive investigation (spirometry, bronchodilator reversibility, FeNO, peak flow variability, eosinophils and bronchial challenge) before and after a trial of inhaled corticosteroid treatment. Asthma diagnosis was confirmed or refuted after evaluating all available data from all visits. Results: Of the 68 participants (mean (SD) age 9.95(3.1) years; 50% male), 47 (69%) were given a diagnosis of asthma. Patients had symptoms for a median of 18 months (IQR 42) before being referred for asthma diagnostic tests. Cough was the most common symptom, occurring in 61 children (90%), 43 (63%) had wheeze, 59 (87%) breathlessness and chest tightness was least common at 37 (54%). There was no significant difference in duration of symptoms in those with asthma (median (IQR) months; 12(41.5)) and those without (18(54); p=0.81). Similarly, there was no significant difference in frequency of symptoms in those with asthma (cough 41/47(87%); chest tightness 26/47(55%); breathlessness 41/47(87%)) compared with those without asthma (cough (20/21(95%), p=0.42; chest tightness 11/21(52%), p=0.82; breathlessness 18/21(85%), p=0.82). There was a trend towards wheeze being more common in children with asthma (33/47(70%) compared to without asthma (10/21(48%), p=0.07). Conclusion: Children had symptoms suggestive of asthma, before treatment, for a median of 18 months prior to being referred for diagnostic testing, resulting in potentially high levels of morbidity. Although no single symptom was able to predict the final diagnosis of asthma, children experiencing wheeze maybe more likely to have asthma and perhaps testing should be considered earlier in such patients.